A pilot study of the metabolic profiles of apheresis platelets modified by donor age and sex and in vitro short‐term incubation with sex hormones. Issue 12 (30th October 2022) - Hadley, Jamie B.; Kelher, Marguerite R.; D'Alessandro, Angelo; Gamboni, Fabia; Hansen, Kirk; Coleman, Julia; Jones, Kenneth; Cohen, Mitchell; Moore, Ernest E.; Banerjee, Anirban; Silliman, Christopher C.
Abstract: Background: Platelets are part of innate immunity and comprise the cellular portion of hemostasis. Platelets express sex hormone receptors on their plasma membrane and sex hormones can alter their function in vitro. Little is known about how age and sex may affect platelet biology; thus, we hypothesized that platelets from males and females have different metabolomic profiles, which may be altered by age and in vitro treatment with sex hormones. Methods: Day 1 apheresis platelets were drawn from five 18–53‐year‐old, premenopausal younger females (YF), five ≥54‐year‐old, postmenopausal, older females (OF), five 18–44‐year‐old younger males (YM), and four ≥45‐year‐old older males (OM). Platelets were normalized to a standard concentration and metabolomics analyses were completed. Unsupervised statistical analyses and hierarchical clustering with principal component analyses were completed. Results: Platelets from OM had (1) elevated mono‐, di‐ and tri‐carboxylates, (2) increased levels of free fatty acids, acyl‐carnitines, and free amino acids, and (3) increased purine breakdown and deamination products. In vitro incubation with sex hormones only affected platelets from OM donors with trends towards increased ATP and other high‐energy purines and decreases in L‐proline and other amino acids. Conclusion: Platelets from OM's versus YF, OF, and YM have a different metabolome implying increased energy metabolism, more free fatty acids, acylcarnitines, and amino acids, and increased breakdown of purines and deamination products. However, only platelets from OM were affected by sex hormones in vitro. Platelets from OM are metabolically distinct, which may impart functional differences when transfused.